Visualizing Energy Transfer at Buried Interfaces in Layered Materials Using Picosecond X‐Rays. (30th June 2020) - Nyby, Clara; Sood, Aditya; Zalden, Peter; Gabourie, Alexander J.; Muscher, Philipp; Rhodes, Daniel; Mannebach, Ehren; Corbett, Jeff; Mehta, Apurva; Pop, Eric; Heinz, Tony F.; Lindenberg, Aaron M.
Abstract: Understanding the fundamentals of nanoscale heat propagation is crucial for next‐generation electronics. For instance, weak van der Waals bonds of layered materials are known to limit their thermal boundary conductance (TBC), presenting a heat dissipation bottleneck. Here, a new nondestructive method is presented to probe heat transport in nanoscale crystalline materials using time‐resolved X‐ray measurements of photoinduced thermal strain. This technique directly monitors time‐dependent temperature changes in the crystal and the subsequent relaxation across buried interfaces by measuring changes in the c ‐axis lattice spacing after optical excitation. Films of five different layered transition metal dichalcogenides MoX2 [X = S, Se, and Te] and WX2 [X = S and Se] as well as graphite and a W‐doped alloy of MoTe2 are investigated. TBC values in the range 10–30 MW m −2 K −1 are found, on c ‐plane sapphire substrates at room temperature. In conjunction with molecular dynamics simulations, it is shown that the high thermal resistances are a consequence of weak interfacial van der Waals bonding and low phonon irradiance. This work paves the way for an improved understanding of thermal bottlenecks in emerging 3D heterogeneously integrated technologies. Abstract : A new nondestructive method is presented to visualize heat transport in nanoscale 2D layered materials using time‐resolved X‐ray measurements of photoinduced thermal strain. This technique is extendable to any crystalline material, including those in confined geometries and active thermal devices, and directly captures the flow of energy across buried atomic interfaces.